(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the interpretation of the chronotope of tragic situations in modern Uzbek novellas through the works of Ulugbek Hamdam and Temurpulat Tillaev. The study examines the artistic and philosophical essence of tragedy, the depiction of death, loneliness, spiritual suffering, and existential conflicts in literary texts. Special attention is paid to the relationship between artistic space and time, the psychological condition of the protagonists, and the symbolic-metaphorical nature of narration.